Individual and community-level determinants of cervical cancer screening in Zimbabwe: a multi-level analyses of a nationwide survey. - Isabirye, Alone; Elwange, Bob Charlestine; Singh, Kavita; De Allegri, Manuela (BMC Women's Health, 2022)
Background: Despite the benefits of cervical cancer (CC) screening to reduce the disease burden, uptake remains limited in developing countries. This study aims to assess the individual and community-level determinants of cervical cancer screening among women of reproductive age in Zimbabwe.Methods: We analyzed data collected from 400 communities from the 2015 Zimbabwe Demographic and Health Survey with a sample size of 9955 women aged 15-49 years. The descriptive statistics and multi-level regression models adjusted for potential covariates were performed to examine the association between individual, household and community-level factors and the uptake of cervical cancer screening in women.Results: The mean (SD) age of women in Zimbabwe using cervical cancer screening was 27.9 (9.9) years. A relatively small proportion of women, i.e., only 13.4% had ever screened for cervical cancer, with higher screening rates observed in the following sub-groups: middle aged women 31-49 years (odds ratio (OR) = 2.01; 95% confidence intervals (CI) 1.72-2.34), and currently working (OR = 1.35; 95% CI 1.17-1.55), those with health insurance (OR = 1.95; 95% CI 1.63-2.34), used modern contraceptives (OR = 1.51; 95% CI 1.22-1.86), exposed to multiple media (OR = 1.27; 95% CI 1.03-1.58), those living in communities that had a high predominance of women with favorable attitude towards Intimate Partner Violence (IPV) against women (OR = 1.21; 95% CI 1.04-1.41) and a non-poor wealth index (OR = 1.54; 95% CI 1.14-2.05).Conclusions: Our data shows a significantly low prevalence of cervical cancer screening among reproductive age women in Zimbabwe. To increase the uptake of cervical cancer screening, there is an urgent need both to implement behavioral interventions targeted at women from low socio-economic groups and to advocate for universal health coverage that includes financial risk protection to help all women realize their right to health.